Prevalence and treatment pattern of Parkinson's disease dementia in Korea. Issue 2 (5th February 2015) - Oh, Yoon‐Sang; Kim, Joong‐Seok; Park, In‐Seok; Shim, Yong‐Soo; Song, In‐Uk; Park, Jeong‐Wook; Lee, Phil‐Hyu; Lyoo, Chul‐Hyung; Ahn, Tae‐Beom; Ma, Hyo‐Il; Kim, Yong‐Duk; Koh, Seong‐Beom; et al.
Abstract : Aim: The aim of the present study was to investigate the point prevalence of dementia and mild cognitive impairment (MCI) in patients with Parkinson's disease (PD). Methods: A total of 1200 patients with PD from 12 hospitals were included in the study. All patients were grouped into normal cognition, MCI and dementia subgroups. General cognitive status and dementia severity were assessed by the Korean version of the Mini‐Mental State Examination, Clinical Dementia Rating and Global Deterioration Scale, and parkinsonian motor status was assessed by the Hoehn and Yahr staging score. Associated sleep behaviors and other medical conditions were checked. Prescribing patterns of antidementia medications were analyzed. Results: Cognitive impairment was frequent in patients with PD; MCI was found in 38.9% of patients, whereas dementia was in 38.3% of patients. The prevalence of cognitive impairment increased with increasing age and longer disease duration, and the symptoms of postural instability and symptoms mimicking rapid eye movement sleep behavior disorder were associated with cognitive impairment. Many dementia patients (95.2%) and 23.6% of MCI patients were treated with antidementia drugs, with rivastigmine the most frequently used. Conclusion: The point prevalence of cognitive impairment in patients with PD was 77.2%. Cognitive impairment was associated with age, disease duration and specific parkinsonian motor/non‐motor symptoms. Over 90% of the patients with dementia were treated with antidementia medication, and rivastigmine was the most frequently used for the management of dementia.Geriatr Gerontol Int 2016; 16: 230–236.